2009
DOI: 10.1136/bjo.2008.152553
|View full text |Cite
|
Sign up to set email alerts
|

Optical coherence tomographic patterns in diabetic macular oedema: prediction of visual outcome after focal laser photocoagulation

Abstract: DRT patients achieved a greater reduction in retinal thickening and greater VA increases than CMO and VMIA patients. We suggest that classifying DMO structural patterns using OCT might allow visual outcome to be predicted after laser photocoagulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
36
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(39 citation statements)
references
References 25 publications
3
36
0
Order By: Relevance
“…Although SRD is often considered a poor prognostic indicator in DMO, previous studies on the prognostic value of SRD in DMO have reported conflicting observations. 4,31 Localised macular oedema (less than four parafoveal quadrants) responded better to grid laser than when all four quadrants were involved, supporting a previous study. 8 Our study also showed that eyes with moderate AMT of 300-350 mm had the worse response to laser, unlike the findings noted by Estabrook et al 32 We hypothesise that moderate thickening do not benefit from a quick response compared with those with o300 mm oedema and those with severe oedema of 4350 mm thickening.…”
Section: Discussionsupporting
confidence: 76%
See 3 more Smart Citations
“…Although SRD is often considered a poor prognostic indicator in DMO, previous studies on the prognostic value of SRD in DMO have reported conflicting observations. 4,31 Localised macular oedema (less than four parafoveal quadrants) responded better to grid laser than when all four quadrants were involved, supporting a previous study. 8 Our study also showed that eyes with moderate AMT of 300-350 mm had the worse response to laser, unlike the findings noted by Estabrook et al 32 We hypothesise that moderate thickening do not benefit from a quick response compared with those with o300 mm oedema and those with severe oedema of 4350 mm thickening.…”
Section: Discussionsupporting
confidence: 76%
“…The most favourable outcome was noted with the DRT group, whereas CMO were poor responders. Similar results have been obtained with other forms of therapies for DMO, 4,[25][26][27] suggesting that the vertical cell-cell alignment of the retinal layers is crucial for positive outcomes to any form of therapeutic intervention. In fact, a recent study showed that the cross-sectional area of retinal tissue between the plexiform layers in CMO on OCT is the best indicator of visual function.…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…Kim et al 13 have asked the question whether specific OCT patterns were predictive of visual outcome after focal laser photocoagulation in DMO. They have concluded that DRT pattern was associated with a greater reduction in retinal thickening and better visual acuity improvement compared with CMO pattern.…”
Section: Resultsmentioning
confidence: 99%